Державно-приватне партнерство у сфері створення та функціонування оптових ринків сільськогосподарської продукції в Україні - Батигіна, О. М. (Право, 2016)
The article outlines the legal and institutional factors and modern scientific approaches to implementing the public-private model of wholesale markets of agricultural products development. The author represents the peculiarities of international experience in public-private partnership in the chosen field. // У статті окреслюються правові й інституційні чинники та сучасні наукові підходи до реалізації громадської приватної моделі оптових ринків розвитку сільськогосподарської продукції. Автор представляє особливості міжнародного досвіду у державно-приватному партнерстві у вибраній галузі.
Public-private partnership in the field of establishment and functioning of agricultural production wholes ale markets in Ukraine
Keywords: public-private partnership; agrarian market; agricultural production wholesale market; державно-приватне партнерство; аграрний ринок; оптовий ринок сільськогосподарської продукції